(untitled) (Research, Society and Development, 2020)
The practice of the violation and the consequences imposed on its author is one of the most debated issues in Brazil, today. Everyone has an opinion on the subject, with convincing arguments based on common sense for any thesis that it is intended to defend the need to deepen the understanding of what actually determine certain deviant behavior and the legal implications the authors has been the subject of several studies which invariably point default behavior arising from common factor that most young offender are submitted. The relationship between an offense, reiteration and victimization by homicide teens considering themselves to applying educational measures was the object on this study. The research model used was based on the verification and confrontation of quantitative and qualitative data conducting interviews with professionals and adolescent abiding educational measures. The results of this study indicate that the dynamics of care to the adolescent offender deployed in metropolitan Belem remains unsuccessful with respects to its main objective, namely: the rehabilitation and victimization for murder of these teens present -if a result natural infractions of their practices.